Changes in prostate cancer incidence in 50–75-year-old men in Lithuania 2006–2009: effect of early diagnosis program - ADOMAITIS, Robertas; JANKEVICIUS, Feliksas; SMAILYTE, Giedre; LEVULIENE, Ruta (Acta medica Lituanica, 2011)
Background. The Lithuanian Prostate Cancer Early Diagnosis Program (LPCEDP) was launched in 2006. Our study aimed to evaluate the PSA testing offered by general practicians for prostate cancer screening as its results may differ from those reported in randomised screening studies. Materials and methods. In the LPCEDP, GPs offered a PSA (prostate-specific antigen) test for informed men aged 50–75 years. A PSA > 3 ng/ml was a cut-off limit for referral to urologist. The study group comprised men aged 50–75 years, diagnosed with prostate cancer in 2006–2009. The Lithuanian Cancer Registry data: age at diagnosis, date of diagnosis, clinical stage. The state Patient Fund data: dates of PSA testing in the LPCEDP. The distribution of clinical stages of prostate cancer was analysed in the following age groups: 50–54, 55–59, 60–64, 65–69, 70–75 years. The incidence rate was expressed as cases per 100000 men per year. The logistic regression model was used to assess the effect of the LPCEDP. Results. In 2006–2009, early prostate cancer accounted for 60.9% of incidence in the study group. The LPCEDP resulted in a sharp rise of the incidence of prostate cancer in 2007, followed by a gradual decline. Major changes in stage II and III tumour incidence resulted in stage migration. The peaks of total prostate cancer incidence and stage II cancer incidence among men aged 65–75 years coincided. In all age groups except 50–54 years, the incidence of stage III prostate cancer followed a downward trend since 2006. The logistic regression model showed that using the LPCEDP significantly increased the chances of men to be diagnosed with prostate cancer at an early stage. Conclusions. The LPCEDP has resulted in a high incidence of prostate cancer (especially of stage II) in men aged 65–75 years. A steady decline of stage III prostate cancer incidence was observed. Men aged 50–54 years cannot benefit from the LPCEDP as they seldom come to GPs. In the current situation, overdiagnosis and overtreatment in men aged over 65 years may overshadow the benefits of timely PSA testing in younger men. Keywords: prostate cancer, early diagnosis, PSA